Cortical Cross Sectional Geometry of Tibia from a Skeletal Series of Natives from Brazil - Suby, Jorge Alejandro (2011)
The aim of this work is to study the cortical cross-sectional geometry of tibias of individuals from a past Tenetehara population in order to explore the sex-related activity patterns in lower limbs in the initial moments of the contact. Total area, cortical area, second moments of area and polar moment of cross-section of tibias were estimated from computed tomography (CT) images. The results showed significant differences in mechanical demand be-tween sexes. Although several individuals revealed signs of cortical resorption in CT imag-es, the results indicate that this population was be exposed to a moderate nutritional-metabolic stress, supporting previous researches conducted in the same sample.